One year mortality after hospital admission as an indicator of palliative care need in the Western Cape, South Africa: an incident cohort study - Frankenfeld, Petronella (Department of Medicine, 2020)
Background: Globally there is an increasing awareness of the need for end-of-life care and palliative care in hospitalized patients that are in their final year of life. However, limited data are available in low and middle income countries which hinders the design and implementation of effective policies and health services for this patient group. Aim: To determine the proportion of patients who die within one year from their date of admission to hospital in public hospitals in South Africa. Design: Retrospective incident cohort study using record linkage of admission and mortality data. Setting: 46 acute care public hospitals in the Western Cape Province of South Africa. Results: Of the 10 761 patients (median age 44 years; IQR: 31 - 60) admitted to 46 hospitals over a 2 week period in March 2012, 1570 (14.6%) died within one year, the majority of the deaths occurring within the first 3 months. Mortality rose steeply with age as expected. The median age of death was 57.5 years; IQR: 45 - 70. A greater proportion of patients admitted to medical beds died in one year (21.3%) as compared with surgical beds (7.7%). Conclusion: Despite a median age under 60 years at admission, a large percentage of patients admitted to public sector hospitals in South Africa, an upper-middle income country with a high HIV and non-communicable disease burden, are in the final year of their lives. This finding highlights the need for planning and implementation of end-of-life and palliative care strategies for hospitals and patients.